“No coração da sala de aula": tensões de gênero no trabalho de docentes mulheres - Ferreira, Letícia Gracielle Vieira (2020)
This research is inserted in the field of investigation of gender relations and their inequalities. In general, in the world of work, women face many challenges in the spaces in which they develop their professional activities. In the academic environment, specifically in higher education classrooms, the relationships established between teachers and students can be inserted in a process of articulation of power that emerges from an androcentric social dynamic, in which experiences of unequal treatments are often experienced, violence and symbolic domination. In this sense, the objective of this research is to understand the gender tensions that emerge from the relationships between female teachers and students in the classrooms of a Public Higher Education Institution. Based on this objective, and with a view to achieving it, we chose post-structuralism as an epistemological and methodological perspective. For Post-structuralism, gender is a regulatory device that, in a historical and localized way, produces the possible identities for the representation of male and female. As a qualitative method, we opted for a field research instrumentalized by the application of semi-structured interviews with female teachers. The research corpus was produced from the experiences of 20 female teachers at the Federal University of Triângulo Mineiro (UFTM). The analysis of the interview transcripts was carried out by analyzing the Foucaultian discourse. The IRAMUTEQ software was used as a resource to support the proposed discursive textual analysis. As a result of this research, it was observed that the relationships between female teachers and students in the classroom reveal certain power practices both as a daily practice of the exercise of the teaching career in the context of the classroom, which, when generated, is configured as an experience that is lived differently for men and women, as a product that reflects the production of subjects and identities based on power relations. The four discursive formations reflect a system of order and male domination that is maintained and updated by government practices within the power field of the teaching career in higher education that are mediated by the field's true regimes.